Patient Satisfaction, Functional Outcomes, and Implant Survivorship in Patients Undergoing Customized Cruciate-Retaining TKA. Issue 9 (September 2021) - Schroeder, Lennart; Pumilia, Cyrus Anthony; Sarpong, Nana O.; Martin, Gregory
Abstract : Background: Customized total knee arthroplasty (C-TKA) systems are becoming increasingly popular in patients with end-stage knee arthritis. Manufactured with use of patient data derived from computed tomography or magnetic resonance imaging, these systems aim to restore the individual bone anatomy of the patient by providing customized fit and geometries. This retrospective study investigated implant survivorship, patient satisfaction, and functional outcomes following C-TKA with a cruciate-retaining prosthesis. Methods: We retrospectively reviewed data from 540 knees in 433 patients who underwent C-TKA performed by a single surgeon at a single institution. Patient demographics, surgical variables, complications, and reoperations were evaluated. Follow-up evaluations were performed via a single telephone call to assess patient satisfaction, functional outcomes according to the Knee injury and Osteoarthritis Outcome Score for Joint Replacement (KOOS-JR) questionnaire, and implant survivorship following C-TKA. Descriptive statistics were analyzed. Results: At the time of C-TKA, the mean age was 71.8 years and the mean body mass index was 29.1 kg/m 2 . The mean follow-up was 2.8 years. Patient satisfaction was high, with 89% of C-TKA patients being either satisfied or very satisfied. The mean KOOS-JR was 82. There were 8 revisions (1.5%) at an average of 0.7 years after the index C-TKA; hence, there was an implant survivorship of 98.5%. Conclusions: To our knowledge, this was the largest retrospective study to date to report on patient satisfaction, functional outcomes, and implant survivorship following C-TKA. We observed a high satisfaction rate, satisfactory functional outcomes, and high implant survivorship at midterm follow-up. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.